Content Management Systems, Bittorrent Trackers, and Large-Scale Rhetorical Genres: Analyzing Collective Activity in Participatory Digital Spaces. (January 2016) - Lewis, Justin
Scholars of rhetoric and writing have long recognized the mediated nature of rhetorical action. From Plato's early indictments of writing as enemy of memoria to Burke's recognition of instrumental causes to recent analyses of digital mediation, the study of meaning-making refuses one-to-one, transparent theories of communication, instead recognizing that there is more to rhetorical action than humans. This article follows the trail of Haas, Swarts, and others arguing that analyses of mediation uncover much about human motives, digital communities, and rhetorical action. I argue that technologies often function as rhetorical genres, providing what Miller characterizes as "typified rhetorical actions based in recurrent situations" that occur in uniquely digital spaces. Working from sites of participatory archival creation and curation, I argue that invisible rhetorical genres operating at macroscopic levels of scale are central to shaping individual and communal activity in sites of distributed social production. To support this claim, I investigate two applications—a content management system called Gazelle and a bittorrent tracker called Ocelot—to demonstrate how largely invisible server-side software shapes rhetorical action, circumscribes individual agency, and cultivates community identity in sites of participatory archival curation. By articulating content management systems and other macroscopic software as rhetorical genres, I hope to extend nascent investigations into the medial capacities of digital tools that shape our collective digital experience.